126 A scoping review of the implementation of non-medical devices for the self-management of chronic breathlessness. Issue Volume 11: Issue (2021)Supplement 1 (16th March 2021) - Prihartadi, Aliya Syahreni; Licastro, Giovanna Impelliziere; Pearson, Mark; Johnson, Miriam J; Luckett, Tim; Swan, Flavia
Abstract : Background: Non-medical devices such as the handheld fan (fan), mobility aids and inspiratory muscle training (IMT) devices offer important benefits for patient self-management of chronic breathlessness. We examined the published evidence regarding barriers and facilitators to implementation of non-medical devices for the self-management of chronic breathlessness from the perspectives of patients, carers and clinicians. Methods: MEDLINE, EMBASE, SCOPUS, EBSCO and the Cochrane Database of Systematic Reviews were searched. Papers were imported into EndNote and Rayyan for review against a priori eligibility criteria. These were; i) any study design including randomised controlled trials, observational, interviews, primary and secondary analyses of data, ii) patients; adults with chronic breathlessness, carers', and clinicians, iii) exposure to the fan, mobility aids and IMT devices, iv) and outcome data regarding implementation of these devices for self-management of chronic breathlessness. Data relevant to use were extracted and categorised as potential implementation barriers and facilitators, and a narrative synthesis exploring reasons for similarities and differences conducted. Results: Seven studies were included; five fan and two mobility aid (wheeled walkers with seats) studies. All of the studies presented patient use of non-medical devices only. The fan was implemented for self-management of chronic breathlessness at home whereas mobility aids were used mainly for outdoor activities. Key barriers to implementation of non-medical devices were: appearance; credibility; self-stigma; technical specifications. Common facilitators were ease of use and feeling safe and secure with the device. Conclusion: Limited evidence exists for the implementation of non-medical devices by patients for the self-management of chronic breathlessness. We highlight the lack of studies on carers, clinicians, IMT devices and the use of applied implementation science theory. Further implementation research is needed to explore the interactions between patient, carer and clinician perceptions of non-medical devices and, ultimately whether this influences the benefits for patient self-management of chronic breathlessness.